Representation of Associative Meaning in Dompak Sinaga™s Love Song Lyrics - Rajagukguk, Intan A; Bahri, Syamsul (Universitas Negeri Medan, 2021)
This study aimed to investigate the associative meanings used in Dompak Sinaga™s Love Song Lyrics, describe the application of associative meanings on the lyrics, and explain the reason for using the most dominant types of associative meaning in Dompak Sinaga™s Love Song Lyrics. The study was conducted using a textual analysis. The data of the study was taken from the lyrics of Dompak Sinaga™s Love Song in the form of written text. The data analysis was taken by coding and theme developing based on the theory proposed by Braun and Clarke (2006). The findings indicated that all the types of associative meaning are found in Dompak Sinaga™s Love Song Lyrics. Based on the research results, the most frequently types that found are connotative meaning and affective meaning. The types of associative meaning in Dompak Sinaga™s Love songs used in different ways. Connotative meaning used using art in the Batak language. The social meaning used by showing or introducing cultural customs which are the songwriter's social background. Affective meaning used by conveyed the songwriter's feelings. Reflected meaning used by conveyed words or lyrics that have multiple conceptual meanings in Batak Toba culture. Collocative meaning used by conveyed words or lyrics that are in the same ˜environment™. The reason to used the dominant types of associative meaning are to make the lyrics of the songs sound softer, to avoid the monotonous and to deliver the message of the songs.